EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Education in times of climate change: Easing learning to build a climate-protection culture - Hernández, Francisco Heras (Mètode Revista de difusió de la investigació, 2015)
Climate change presents significant educational challenges: it is necessary to know about its causes, to recognise the roots of the problem and to be aware of its consequences. This is necessary to build a more realistic perception of climate risks and better understand our vulnerabilities. But it is especially important to know about the solutions; urgent training is needed to build a «low-carbon» culture to prevent dangerous interference with the global climate. Educational institutions – both formal and informal – must consider their contribution to these needs for knowledge and social change, because climate change will impact our future heavily and because everyone plays a role in the complex network of responsibilities that fuel it.

Considering EdTech in climate emergencies: To what extent and when is it feasible? - Mazari, Haani; Baloch, Imdad; Riley, Matthew; Riley, Haani Mazari, Imdad Baloch and Matthew (EdTech Hub, 2022)
New research from EdTech Hub explores the response to climate emergencies following the Pakistan floods - the worst in recent history - and highlights the importance of utilising existing, most accessible technologies to ensure learning continuity.

Climate Change and Education: From evidence to action - Fitzpatrick, Rachael; Amenya, Donvan; McAleavy, Tony (Education Development Trust, 2024)
Over the past ten years, the world’s poorest countries have experienced nearly eight times as many natural disasters compared to three decades ago. This report considers the impacts of the global climate emergency on school education in low-income countries, and explores how to address the negative consequences it has on learning.

A systems thinking approach to e-learning on climate change: Capacity-building for junior high school teachers in the Philippines - Ignacio, John Trixstan Santos; Gonzales, Charlotte Kendra Gotangco; Lee-Chua, Queena (International Journal of Disaster Resilience in the Built Environment, 2023)
A mixed-method study was performed to determine the impact of integrating systems thinking (ST) into an electronic learning module for junior high school teachers in the Philippines. The study aims to assess how an ST approach to pedagogy compared against a conventional approach in terms of contribution to the participants’ global climate change content knowledge, holistic thinking and depth and accuracy of knowledge and reasoning.,The study implemented e-learning modules using an ST approach versus a conventional approach in teaching climate science to junior high school teachers. The paper presents quantitative data obtained from pre and posttests results of the 20 teacher-participants and qualitative data obtained during the focus-group discussion (FGD) after the implementation of the study.,The results from the statistical analysis indicated that the ST group obtained a significant increase in their assessment scores compared to the non-ST group, according to predetermined criteria. Content knowledge, depth and accuracy of knowledge and reasoning increased the most. The participants mentioned during the FGD that the module helped deepen their understanding of climate change.,The study was limited to 20 teacher-participants, but it has relevance for public school teachers in the country given that participants had raised concerns regarding the lack of training in their schools for teaching climate science. They admitted that they lacked critical information to include in climate change topics in their classes.,This paper shows how the ST approach can be used to teach climate change to junior high students. The e-learning module can provide teachers with better understanding, knowledge and reasoning to teach climate change to high school students more effectively.

Why East Africa’s education systems must build climate resilience now: Three takeaways from a conference - Mbugua, Ciku; Simmons, Hannah; Barretto, Johnpaul; Barretto, Ciku Mbugua, Hannah Simmons and Johnpaul (EdTech Hub, 2024)
How can education systems build resilience to climate change? EdTech Hub explored this critical question at the inaugural East African Community Education Conference, held in Arusha this August. Discover our key insights in this blog.

What Can the Education Sector Do to Adapt to the Forthcoming Impacts of Climate Change? - Proctor, Jamie (Global Partnership for Education, 2023)
Practitioner experience and reflections on what can be done specifically within the education sector to adapt and reduce the negative impacts of climate change on education.

Climate, education, and AI: Challenges and opportunities - Haßler, Björn; Taruza, Takudzwa Charisse; Zainab Akhtar; Charrad, Mohammad; Dube, Gugulethu; Huntington, Bethany; Jengo, Eunice; Lester, Jennie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Three Take-Aways on Climate Resilience for Education Systems in East Africa - Simmons, Hannah; Mbugua, Ciku; Barretto, Johnpaul (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Leaving no-one behind: Improving climate change and entrepreneurship education in sub-Saharan Africa through E-learning and innovative governance systems - Chirambo, Dumisani (Climate Literacy and Innovations in Climate Change Education: Distance Learning for Sustainable Development, 2018)
Poverty and climate change vulnerability is increasing in Sub-Saharan Africa (SSA) because the region lacks education and skills development facilities, and sustainable governance systems. Arguably, mainstreaming climate literacy in secondary schools through Information and Communications Technology (ICT) modalities can promote sustainable development and climate change resilience by providing early opportunities for the youth to gain knowledge and awareness of the behavioral and cultural changes that may foster improved climate change resilience. Through an inductive analysis based on research articles, case studies, policy briefs, and academic literature reviews, this chapter sought to highlight emerging ICT learning contexts in SSA as a means to determine the extent to which ICT may be used to promote climate change and sustainable development education in secondary schools. The chapter showed that climate literacy at secondary schools was being constrained by a lack of climate change education material and content on existing ICT learning platforms; and a lack of innovative governance systems to support governments in delivering climate literacy content to secondary schools and the youth. Consequently, to “leave no-one behind” requires non-state actors to develop and utilise innovative governance systems and digital climate literacy material that can complement government efforts to mainstream climate literacy at secondary schools.

Getting ahead of climate hazards: Education cannot wait and strategic partners accelerate anticipatory action - Education Cannot Wait (2024)
As world leaders gather for the United Nations General Assembly and Summit of the Future, Education Cannot Wait (ECW) announced two ground-breaking anticipatory action pilots in Pakistan and Somalia.

Distance learning will enable climate refugees to avoid falling into the social risk trap - García, María del Pilar Quicios; González, Ana Huesca; Sevillano, María Ángeles Pascual (Climate literacy and innovations in climate change education: Distance learning for sustainable development, 2018)
This chapter describes how distance learning can help climate refugees protect themselves against the social risk that results from restrictions on their right to education. This documentary analysis is predominantly theoretical, and its general aim it to present a documentary corpus to facilitate classification of climate refugees in terms of their ICT competence. The specific aim is to provide keys for the design of educational programs that can closely match the competences of the individual refugee. This is the novelty and originality of this chapter. The refugee has traditionally been treated as an element within a group to which common educational methodologies are applied. This chapter treats each refugee as an individual according to their ICT skills, so each one will require a specific type of education.

Innovative finance reshaping cyclone resilience and child-responsive disaster management in Madagascar - UNICEF Climate, Environment, Energy and Disaster Risk Reduction (2024)
In Madagascar, severe cyclones have become an integral part of children’s lives. Between 2000 and 2024, more than 50 tropical storms and cyclones have impacted over six million boys, girls and adults. Given that nearly 60 percent of Madagascar’s population (31 million) is under the age of 25, children and young people bear a disproportionate burden.*This case study shows how UNICEF, the Government of Madagascar and civil society are working together to pilot a ground-breaking, innovative finance solution that includes a child-responsive, parametric risk transfer product for tropical cyclones. The Today & Tomorrow approach aims to reduce child exposure and vulnerability to future shocks and hazards, engage children and young people in solutions and strengthen the essential social systems and services they rely on most. In Madagascar, Cyclones Cheneso, Freddy and Gamane and Tropical Storm Alvaro affected nearly 200,000 students. The case study highlights UNICEF Madagascar and government efforts in the education sector to support these students and build disaster resilience in affected communities.*ACAPS, Madagascar, Cyclone Exposure and Vulnerabilities and UNICEF, Child Climate Risk Index (CCRI).

Climate Change and Education in Kenya - Fitzpatrick, Rachael; Amenya, Donvan (Education Development Trust, 2023)
What impact does climate change have on education, especially in areas which are vulnerable to climate disasters and extreme weather events? In this report, we explore the impact of climate change on schools and learning in six counties in Kenya (Nairobi, Mombasa, Turkana, Tana River, Kwale and Kilifi).

Climate Risk Index 2025 - Germanwatch (2025)
The Climate Risk Index (CRI) ranks countries by the human and economic toll of extreme weather. The latest edition highlights increasing losses and the urgent need for stronger climate resilience and action.

Harnessing the Transformative Potential of Education for Climate Change Mitigation, Adaptation and Resilience Building in Europe and Central Asia - UNICEF (UNICEF Europe and Central Asia (ECA), 2023)

Building Climate-Resilient Schools - Institute for Development Impact (2025)
Worldwide, educators are building climate-resilient schools through action planning, infrastructure upgrades, and student engagement.

AI's climate impact goes beyond its emissions - Coleman, Jude (Scientific American, 2023)
To understand how AI is contributing to climate change, look at the way it’s being used

Preparing children for climate-related disasters - Seddighi, Hamed; Yousefzadeh, Sepideh; López López, Mónica; Sajjadi, Homeira (BMJ Paediatrics Open, 2020)
Climate-related disasters affect different dimensions of children’s health and well-being both directly and indirectly. Reducing children’s vulnerability and exposure to climate-related disasters is crucial to protect them against risks. Children as climate-change agents and future leaders at local, national and international level can obviously contribute to reduce vulnerabilities in families and communities and transfer knowledge to them. Moreover, children can advocate for climate change mitigation. In the long term, participation of children in the climate change mitigation programmes may lead to fewer disasters and, consequently, less risk to their health., As government policies have failed to fully address and respond to the drivers of climate-related disasters, disasters preparedness and education for children should be considered an essential activity to protect children from disaster’s risks., Main factors in shaping children’s behaviour and response to disaster are increasing the risk perception and knowledge of the children. When a child perceived likelihood, susceptibility and severity of a disaster (such as earthquake), then they would be able and willing to learn how to prepare for that., So far, disaster education programmes for children have mostly relied on offline school-based training. Different innovative approaches can be applied to continue education within online and digital formats including virtual reality, digital games and online platforms. However, an advocacy support by influential entities such as companies engaged in entertainment industry is required to raise the awareness of public and particularly the children about disaster preparedness.

Addressing the Climate, Environment, and Biodiversity Crises in and Through Girls’ Education - FCDO (FCDO, 2022)
This paper sets out the Foreign, Commonwealth & Development Office vision for how education is viewed in relation to climate and environment change.

Budget 2025-26 from a climate lens - Naeem, Zainab (2025)
By any measure, Pakistan’s federal budget for FY2025-26 represents a notable evolution in the country's approach to climate change.For a country that has endured some of the most brutal...

Classroom social climate, self-determined motivation, willingness to communicate, and achievement: A study of structural relationships in instructed second language settings - Joe, Hye-Kyoung; Hiver, Phil; Al-Hoorie, Ali H. (Learning and Individual Differences, 2017)

Climate-induced Disasters as an Evolving Threat to Southeast Asia's Maritime Security - Gong, Lina (Asia Maritime Transparency Initiative, 2022)
This article is part of Evolving Threats to Southeast Asia’s Maritime Security, a series of analyses produced by experts convened by the S. Rajaratnam School of International Studies. How has the threat of climate-induced disasters evolved over the last 20 years? Natural hazards originating from the oceans such as tropical storms and tsunamis that are […]
Keywords: ⛔ No INSPIRE recid found

Addressing Cross-Cutting Themes in the Use of Education Technology and Digital Learning in Southeast Asia: Recommendations for policy, practice, and research - Swindell, Andrew; Radford, Kate (EdTech Hub, 2025)
Across Southeast Asia, digital learning and EdTech have expanded rapidly in response to long-standing challenges and the Covid-19 pandemic. While access and integration have improved, gaps remain for out-of-school children, girls, learners with disabilities, and those in crisis-affected settings. This paper examines five cross-cutting themes essential to inclusive education: gender equity, special educational needs and disabilities (SEND), school-related violence and bullying, education in emergency and climate-resilient settings, and social and emotional learning (SEL) and mental health and psychosocial support (MHPSS). It offers recommendations for policy, practice, and research to promote flexible, inclusive, and evidence-based approaches to equitable digital learning. Keywords Out-of-school children and youth (OOSCY); Southeast Asia; gender equity; special educational needs and disabilities (SEND); school-related violence and bullying; education in emergencies; social and emotional learning (SEL) An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

Youth Transitions: Creating Pathways to Success - Hughes, Deirdre; Smith, Graeme (Education Development Trust, 2020)
Around the world, young people face considerable challenges. Even before the disruption of the Covid-19 crisis, policymakers were seeking to respond to rapid technological advances, climate change and -- in some countries -- an ageing population and workforce. While children and young people worldwide generally have high aspirations and ambitions for their futures, evidence shows that they often face problematic and protracted transitions into work. In this context, new pathways from school to employment are needed. In this paper, we review extensive evidence to provide guidance on how children and young people can be best prepared to succeed in their school-to-work transitions, both now and in the future.
Keywords: 21st Century Skills; COVID-19; Career Development; Career Education; Economic Climate; Education Work Relationship; Educational Policy; Employers; Foreign Countries; Job Skills; Labor Market; Pandemics; Public Policy; Social Change; Technology Uses in Education; Vocational Education; Youth Employment

Towards Climate Resilient Education Systems - Kagawa, Fumiyo (UNICEF Regional Office for South Asia, 2022)

Climate Change Impact on Education - Weng, Boey Chun; Morooka, Rina; Mujtaba, Rustam Shariq; Shitong, Yang (Aide et Action, 2020)
Research report done for Aide et Action On selected ASEAN Countries (Cambodia, Vietnam, Laos PDR)
Keywords: Added through targeted search; ⛔ No DOI found; ⛔ No INSPIRE recid found

Education and Climate Change: How to develop skills for climate action at school age? - Bos, Maria Soledad; Schwartz, Liora (Inter-American Development Bank, 2023)

Climate Change Education and Curriculum Revision - Teixeira, Janssen Edelweiss; Crawford, Elizabeth (World Bank, 2022)

Leveraging Education in Emergencies for Climate Action - EiE Hub (Geneva Global Hub for Education in Emergencies, 2023)

Choosing our future: Education for climate action - Sabarwal, Shwetlena; Venegas Marin, Sergio; Spivack, Marla; Ambasz, Diego (The World Bank, 2024)

Promoting Climate-Sensitive Early Childhood Care and Education in Emergencies - INEE (Inter-agency Network for Education in Emergencies (INEE), 2023)

Not Just Hot Air: Putting climate change education into Practice - UNESCO (UNESCO Digital Library, 2015)

Climate Change Education for a More Sustainable, Just and Gender Equal World - Plan International (Plan International, 2024)

Acting Now for Tomorrow: Addressing Climate Mobility Challenges in Southeast Asia - Ysmael Arriola, Sarah Lou (The ASEAN, 2024)

Empowering community resilience to climate change in Cameroon using technology-enhanced learning - Sidze, Sandrine Meguieng (Dresden University of Technology, 2016)
Located in Central Africa, Cameroon is considered the driving force of the sub-region due to its strategic location in the center of the African continent. During the last five years, the country has been under the constant threat of a large range of disasters like floods, droughts, landslides, epidemics, etc. In such a context, the government is implementing several strategies for Disaster Risk Reduction in the country. Under the lead of the Ministry of Territorial Administration and Decentralization, the Directorate of Civil Protection, coordinates Disaster Risk Reduction activities through a network of over 379 decentralized institutions and international partners (Ayanji, 2004). Despite a high level of deployment, these activities still prove to have a low level of efficiency on the field. Results from the literature review suggest that this may be due to strategies for public education and public awareness that do not mirror stakeholders’ needs, capacities, and background. There is a need to: (1) identify the failures of the pre-existing public education and public awareness strategy, (2) assess the educational needs and capacities of each category of actors, (3) select adequate instructional methods and tools and (4) ensure the effectiveness and sustainability of the newly proposed strategy.

Understanding urban climate change and digital infrastructure interventions from a resilience perspective - Heeks, Richard; Ospina, Angelica (SSRN Electronic Journal, 2013)

Global Climate Risk Index 2021: Who Suffers Most from Extreme Weather Events? - Eckstein, David; Kunzel, Vera; Shafer, Laura (German Watch, 2021)

The Impact of Climate Change on Education and What to Do about It - Marin, Sergio Venegas; Schwarz, Lara; Sabarwal, Schwetlena (The World Bank, 2024)

Build back better: Education must change after COVID-19 to meet the climate crisis - Giannini, Stefania (UNESCO, 2020)

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, A; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.

Asia-Pacific regional synthesis: climate change, displacement and the right to education - UNESCO Digital Library - UNESCO; UNESCO Multisectoral Regional Office in Bangkok; United Nations University Institute for the Advanced Study of Sustainability (2023)

Investing in Science, Technology, Engineering and Math (STEM) Education to Build Africa’s Resilience Against Climate Change - United Nations (United Nations Office of the Special Adviser on Africa, 2024)

Aspirations and the Role of Social Protection: Evidence from a Natural Disaster in Rural Pakistan - Kosec, Katrina; Mo, Cecilia Hyunjung (World Development, 2017)
Citizens’ aspirations are increasingly recognized as an important dimension of their well-being. Those with high aspirations set ambitious goals for themselves, and those with low aspirations may fall prey to a poverty trap. Do natural disasters negatively impact aspirations? If so, can governments blunt these effects? We consider Pakistan’s devastating 2010 floods—and the government’s uneven relief efforts—to analyze these questions. We first show that the extreme rainfall generating this disaster significantly reduced aspirations, even when current levels of household expenditure, wealth, and education are taken into account. Individuals experiencing 2010 monsoon season rainfall that was one standard deviation higher than average had aspiration levels 1.5years later that were 0.15 standard deviations lower than those of similar individuals experiencing just average levels of rainfall. This is the same negative shock to aspirations that one would experience as a result of a 50% reduction in household expenditures. Moreover, the negative effect of natural disasters on aspirations is especially strong among the poor, and among those who are most vulnerable to weather shocks. However, exploiting exogenous variation in flood relief access, we show that government social protection can attenuate these negative impacts. Individuals in villages that received Citizens Damage Compensation (Watan Card) Program flood relief—providing cash equivalent to 9.4% of annual household expenditures in each of the three years following the disaster—saw significantly lower declines in aspirations than did those in similarly affected villages without this relief. This offers a new understanding of social protection; it not only restores livelihoods and replaces damaged assets, but also has an enduring effect by easing mental burdens, and thus raising aspirations for the future. The negative effects of natural disasters and the efficacy of government relief programs may thus be underestimated if aspirations are ignored.
Keywords: Pakistan; South Asia; climate change; political economy of development; political psychology; state capacity

Revised Pakistan 2022 Floods Response Plan: 01 Sep 2022 - 31 May 2023 - UNOCHA (2022)
Appeal in English on Pakistan about Agriculture, Climate Change and Environment, Flash Flood, Flood and more; published on 4 Oct 2022 by OCHA

Drought situation in the Kenya ASAL areas now at crisis level - Kenya | ReliefWeb - ASAL Humanitarian Network (2022)
News and Press Release in English on Kenya about Agriculture, Climate Change and Environment, Drought and more; published on 5 Oct 2022 by ASAL Humanitarian Network

Low-cost emerging technologies as a tool to support informal environmental education in children from vulnerable public schools of southern Chile - Alò, Dominique; Castillo, Andrea; Marín Vial, Paula; Samaniego, Horacio (International Journal of Science Education, 2020)
Reform to the Chilean educational system seeks to improve public education, adapting the school curriculum to new technologies and the information revolution. Our study focused on highlighting potential issues with environmental and technological education, offering opportunities to complement the current Chilean curriculum with an interdisciplinary approach. During a five-week period interspersed through the school semester, 115 underprivileged children in seventh grade from five public schools of southern Chile participated in workshops based on Arduino technology to address current environmental problems caused by global change and anthropization. Surveys were conducted to participating students and included both open and closed-ended questions, which measured attitudes and perceptions towards science and the use of technology in classrooms and daily lives. Surveys were analysed quantitatively with basic statistics and qualitatively by building semantic networks of the relationships between different concepts expressed by the students. Results did not show significant changes in attitudes towards science or technology before and after the workshops but students reported mixed feelings about science. Indifference and fear emerged, coupled with the need for more interactive experiences. Curiosity and enthusiasm also surfaced when students were using new technologies. Since the school curriculum is generally focused exclusively towards the completion of specific curricular aims, highly vulnerable schools in Chile have few opportunities to access interactive, hands-on activities. Low-cost, emergent technologies, such Arduinos, have a high potential for improving student's attitude towards science and technology and their use should be considered when tailoring school curriculum in Chile and elsewhere.
Keywords: 21CC abilities; Arduino; climate change; hands-on; information and communication technology; project-based learning

Mega risks, education, knowledge, and sustainability - Khan, Mohammad Aslam (Cities and mega risks: COVID-19 and climate change, 2022)
This chapter presents the crises urban education systems are facing across the world due to mega risks. The pandemic has caused the largest disruption in history in education affecting 1.6 billion students in about 190 countries. Simulations of learning losses show that the current generation of students may have lost an estimated 17 trillion US dollars in lifetime earnings at present value due to the pandemic alone—equivalent to 14% of today’s global GDP. Climate change has also affected cities world over with recurring climate-related extreme events like cyclones and floods through destruction of schools, relevant infrastructure, and learning materials. Indirectly they impact family livelihood and well-being by affecting health, food, and shelter—resulting in increased absenteeism, dropouts, and deteriorating quality of learning. Again, their financial impacts are believed to be in trillions of dollars. Besides learning losses, school closures also affect the growth and development of children by denying them school meals, health services including vaccinations, and psychosocial support. In terms of response, school closures increased the reliance of institutions upon remote technology—digital solutions or broadcast media like radio and television. This chapter besides highlighting key obstacles in a shift to distance learning or adapting to new normal also discusses the lessons learnt and emerging opportunities. It emphasizes speeding up reform and preparing future generations to be both productive and resilient to face mega risks through education and practice.

Reimagining our Future: Building Back Better from COVID-19 - UNICEF (2020)
This report presents the need to link COVID-19 recovery and response to climate and environmental action and details UNICEF's proposed solutions to reduce the impact of COVID-19 that can at the same time create a foundation for a greener, more sustainable future for children.
Keywords: ⛔ No INSPIRE recid found

World Bank makes 10-year plan with Pakistan for $20 billion in funding - Greenfield, Charlotte (Reuters, 2025)
Pakistan's prime minister on Wednesday welcomed a first-of-its-kind agreement with the World Bank for a plan to focus $20 billion in lending to the cash-strapped nation over the coming decade on development issues like the impact of climate change as well as boosting private-sector growth.

Ed-Tech Within Limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ?greening? of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ?abundant? forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ?Ed-Tech Within Limits? might be pursued ? outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.

Ed-tech within limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ‘greening’ of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ‘abundant’ forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ‘Ed-Tech Within Limits’ might be pursued – outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.

State of Education for Crisis-Affected Children and Adolescents: Access and learning outcomes - Education Cannot Wait (2025)
Education Cannot Wait's State of Education for Crisis-Affected Children and Adolescents: Access and Learning Outcomes – Global Estimates 2025 Update reveals that the number of school-aged children in crises worldwide requiring urgent support to access quality education has reached 234 million – an estimated increase of 35 million over the past three years. Intensifying conflicts, climate-induced disasters and other crises are fueling these trends.  Refugees, internally displaced children, girls and children with disabilities remain among those most impacted.

High-quality education for better sustainability and resiliency - Prazian, Michael V; Prykhodko, Viktoria M (IOP Conference Series: Earth and Environmental Science, 2023)
The world meets poly crises in climate, pandemic, energy, food, human rights, and migration; hot and cold wars have come in Europe and other regions. The scope of the tasks becomes unprecedented, and their complexity demands high-level skill sets and teaching culture. Education moves into epicentres of the fight for better sustainability and resilience. The United National Sustainable Development Goals Four (SDG4) supposes allocating and diligently using several trillion US dollars for the next decades. The ambitious goals drive the educational system to be at a decent level regarding outcome and process. Saving gratitude to functions of a fundamental human right, a public good, gender equality, and an absolute right to education for all, the author urges that high-quality education is the priority because it will help society to cope with a new level of challenges and even existential threats the climate-like. The article describes the methodology and the importance of soft-hard skills for teaching and learning. The secondary-based sources research illustrates practical results regarding the educational process. The Triple Bottom Line principle (Planet, Profit, People) encompasses many disciplines engaging the main aspects of sustainability and resiliency and climate change for the university curricula in a coherent way. The article considers future trends in high education and case studies connected with the European Green Deal, environmental, social, and governance (ESG) reporting and practical aspects of Green Growth and De-Growth Theory. The Quality of Education reflects the regulator’s requirements and social and personal expectations. Life-long learning becomes a norm. The authors consider university products, processes and platforms through the lens of future trends, threats and opportunities. In times of turbulence, the results obtained through students’ upskilling and reskilling programs should fit the demands of new jobs, technologies, and financial mechanisms.

Elements Shaping the South African Education System of the Future - Barends, Heidi (2019)
The South African education system is deeply unjust because a child’s place of birth, skin colour and family’s income largely determines their educational attainment. Understanding future trends and developments can assist stakeholders in planning and decision making. Better decisions could ultimately improve the education system. Therefore, this research aims to answer three questions: What trends could impact the South African education system? What opportunities and threats arise due to these trends? Who could influence the system?  To address these questions, a mixed-method approach was adopted. First, conceptual systems diagrams were developed to depict the current education system and its stakeholders. Then, semi-structured expert interviews were used to identify future trends, threats and opportunities.  This study found that the trends impacting South Africa broadly align with global trends. Examples include an increase in privatisation, technology in schools and climate change. More violence in schools is the main outlier. The study found that the risks related to technology and climate change are not being planned or accounted for. Similarly, violence is currently not a priority. The study also found that participants agreed on who the major stakeholders are, but disagreed on what actions stakeholders should take.
Keywords: Actor Diagram; Basic Education; CLD; Causal Loop Diagram; Education System; Foresight Study; Future Study; Future Trends; South African Education System; Systems Approach; _C:China CHN; _C:Germany DEU; _C:India IND; _C:Japan JPN; _C:Nigeria NGA; _C:Pakistan PAK; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:scheme:1; _not_EdTechHub; _zenodoOTHER

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School factors related to the emotional wellbeing and resettlement outcomes of students from refugee backgrounds: Protocol for a systematic review - Horswood, Deserae; Baker, Jess; Fazel, Mina; Rees, Susan; Heslop, Linda; Silove, Derrick (Systematic Reviews, 2019)
Background: Schools can play a vital role in the resettlement of refugee children and their families. Yet, the body of research examining school environmental factors that support the mental health and acculturation of refugee children is methodologically heterogeneous, investigates numerous and disparate school factors, and is often "hidden" in broader qualitative studies. This limits the capacity to apply the findings in a practical manner. Methods: Based on PRISMA statement principles, we review the relevant literature to investigate the relationship between school climate and the emotional wellbeing and resettlement outcomes of refugee students. Six electronic databases will be systematically searched: MEDLINE, PsycINFO, Embase, CINAL, Web of Science, and ERIC, supplemented by a systematic review of the grey literature, relevant international websites, and sequential, site-specific internet searches. Finally, subject area experts will be consulted and backward and forward citation searches of included articles will be completed. Two independent reviewers will screen identified articles against eligibility criteria and extract data for included studies. Quality of included studies will be assessed using the Mixed Methods Appraisal Tool (MMAT) for mixed studies reviews. Data will be synthesised using a convergent qualitative narrative approach. Discussion: Given the centrality of school in the daily lives of resettled refugee children, it is vital to assess the impact of school climate on the psychosocial wellbeing and resettlement trajectories of this population. This review will identify evidence-based school factors which support good mental health and resettlement outcomes for refugee students and make recommendations for translation of this knowledge into the school environment.
Keywords: Acculturation; Mental health; Refugee; Resettlement; School; Systematic review

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EduCare: Digital Resilience for Displaced Youth - Gautier, Maya; Ciriello, Raffaele F (Australasian Conference on Information Systems 2024: Digital Futures for a Sustainable Society, 2024)
The ongoing crises of geopolitical conflict and climate change have forced millions of children worldwide into displacement, disrupting their education, mental health, and access to food security. This researchin-progress paper reports on the design and evaluation of a mobile solution, EduCare, which aims to address the intertwined needs of forcibly displaced school-aged children. Building upon previous research, EduCare integrates educational resources, mental health support, and nutritional guidance into a cohesive sociotechnical system. Using a design science research methodology, this paper outlines the development process of EduCare, guided by principles of resilience, awareness, and empowerment. The potential of EduCare to enhance the resilience of displaced youth is explored through scenariobased design and evaluation of its desirability, viability, and feasibility. This work contributes to the information systems (IS) literature by offering a novel approach to supporting the complex needs of forcibly displaced youth through a sociotechnical framework.
Keywords: ⛔ No DOI found

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sustaining learner participation and progression through networked schooling: a systemic approach for Mobile Out of School Children - Dyer, C.; Echessa, E. (International Journal of Educational Development, 2019)
Despite repeated calls for education systems to respond flexibly to enable all children to participate in formal education, limited progress has been made for those we term Mobile Out of School Children (MOOSCs). Livelihood-related mobility often precipitates a process of learner drop out during the year. Retention of such children, and reducing the risk of their relapsing into MOOSC status, requires a re-framing of ‘school’ as a spatially dispersed system, or network, to accommodate learner movement. Networked schooling for children in mobile pastoralist communities in Ethiopia embeds formal education within mobile pastoralists’ resource management practices and orientates service provision accordingly. Although it is resource-intensive, networked schooling enables the requisite flexibility to support retention of pastoralist and other mobile learners. It of significant interest to global effort towards leaving none behind, particularly in the global drylands and other contexts where climate change is making learner mobility increasingly complex, and the need for a systemic response ever more pressing.

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 6 Digital technologies and education in Small Island Developing States (SIDS) From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Towards cool cities and communities: Preparing for an increasingly hot future by the development of heat-resilient infrastructure and urban heat management plan - Cui, Yi; Yin, Mingqiang; Cheng, Xiang; Tang, Junqing; He, Bao-Jie (Environmental Technology & Innovation, 2024)
Planning for extreme heat challenges is an urgent task for urban planners, designers, and managers because urban heat is a new normal climate-related challenge for many cities. However, how to integrate existing scientific outcomes and achieve the transformation from research to practice is a critical question. This study aims to frame a heat-resilient infrastructure system and an urban heat management plan (UHMP) to better promote heat solution implementation. This study analyses heat-related challenges, with China as a typical nation with highly urbanized and urbanizing cities, to demonstrate the urgency of preparing for an extreme heat era. This study then elucidates the fundamentals and methods for heat-resilient infrastructure and UHMP development, with a structure of prevention, preparation, mitigation, adaptation, and co-benefits approaches. Heat–resilient infrastructure was framed to ensure that society withstands, responds to, and recovers from heat–related impacts through actions of planning, design, construction, and operation, considering structural measures, non–structural measures, and a co-benefits approach. Furthermore, a UHMP framework was developed by determining the key mission, critical components, and associated agencies. Overall, this study provides planners, designers, and managers with theoretical and methodological frameworks to comprehensively understand heat solutions and increase their implementation capacity.
Keywords: Challenges and opportunities; Heat-resilient infrastructure; Information technology and telecommunication; Preparation, mitigation and adaptation; Structural and non-structural measures; Urban heat management

Investigating Thai teachers attitudes toward students with autism - Little, Cathy; Vibulpatanavong, Kanokporn; Evans, David (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2014)
Greater numbers of students with Autism are being educated in mainstream settings, enrolled in regular classes, placed with ‘regular’ students, and with teachers who often have limited experience or knowledge about their specific disability. Teachers, with limited knowledge of disability, struggle to successfully include these students into their classes. However, a powerful predictor of successful inclusion of students with a disability into mainstream classrooms is the attitude of the general education teacher (Ainscow, 2007). A plethora of research abounds to empirically support what is known about quality teaching practice for students with Autism, yet this same research highlights teachers concerns of lack of knowledge, lack of support systems and overriding legislative policy as primary obstacles to the inclusion process. Research suggests that teachers of students with Autism have limited knowledge about the specific traits and idiosyncrasies that define these students learning styles and behaviours.This research investigated the attitudes of Thai teachers toward their students with Autism. Attitudes were defined by four constructs: attitude toward inclusion, teacher effectiveness, academic climate, and social inclusion. A key premise of this research was that positive teacher attitude was strongly related to more successful outcomes for students. This research utilised a mixed methods design over two phases, using both survey data and qualitative case studies. The following paper reports only on phase one of the research, the responses to the Teacher Attitudes Survey. Participants of the study were 404 teachers from seven schools in Bangkok. Results showed an ongoing need to assist teachers in building their confidence and knowledge in catering for students with Autism in the regular classroom. Teacher confidence (effectiveness) in meeting the education needs of students with Autism was reported as limited, yet teachers reported their understanding about the social inclusion of students with Autism in the regular school setting to be positive. Keywords : Attitudes, Autism, Education, Inclusion, Social Inclusio
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Tackling coloniality in EdTech: Making your offering inclusive and socially just - Adam, Taskeen; Moustafa, Nariman; Sarwar, MoizzaBinat (EdTech Hub, 2022)
On 29 June 2022, Bertha Centre, EdTech Hub, Open Development & Education and the Overseas Development Institute (ODI) presented a workshop on Tackling Coloniality in EdTech. The workshop was hosted by Ntombini Marrengane (Bertha Institute). This slide deck shares the resources and activities used at the workshop, in the hope that it inspires others to host similar workshops that critically reflect on how coloniality can be embedded in EdTech designs, projects, programmes, processes, structures, values, knowledge systems, and philosophies.
Keywords: _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
Keywords: _r:AddedByMyEducationEvidence

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Artificial Intelligence in Education Across Bangladesh: Findings from a rapid scan and key informant interviews - Honda, Delanie; Ahmed, Shakil; Ramesh Vasudevan, Sharanya (EdTech Hub, 2025)
This Helpdesk Report was developed in response to a request from the UK's Foreign Commonwealth and Development Office (FCDO) Bangladesh for a rapid scan on the use of Artificial Intelligence (AI) in Bangladesh’s education system. The report aims to provide education decision-makers with accessible, evidence-based summaries of best practices in specific areas of EdTech, in this case, the AI landscape in Bangladesh. Using a combination of desk research and key informant interviews, the scan provides insights for the FCDO by highlighting key actors, early use cases, opportunities, and challenges, and to support future thinking about AI’s role in education, particularly as Bangladesh is preparing for its next development education plan — the Primary Education Sub-Sector Programme. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Technology-Enabled Psychosocial Support Interventions for Education in Emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode